ANALISIS KOMPARATIF STRATEGI PENETAPAN HARGA GOJEK DAN MAXIM: IMPLIKASINYA TERHADAP LOYALITAS KONSUMEN - Rana Saipullah; Muhammad Firman Hakim; Nayna Carissa Putri Ariefandi; Dwi Desi Yayi Tarina (Jurnal Akuntansi dan Ekonomi Bisnis, 2026)
The development of digital technology in Indonesia has significantly transformed the transportation industry, especially with the emergence of online platforms such as Gojek and Maxim. This study uses a normative legal research method with a library research approach, relying on secondary data from legislation, books, scientific journals, and relevant articles. The results show that Gojek focuses on building a comprehensive ecosystem of services, while Maxim competes through lower fares and simpler offerings, giving consumers diverse and competitive choices. However, this also creates both opportunities and challenges for MSMEs, requiring active government regulation to ensure fair and healthy competition. With appropriate regulation, online transportation is expected to develop sustainably and bring broad economic benefits to Indonesian society.